Biometrical studies on genetic variability and diversity in upland rice (Oryza sativa L.) - S. Muthuramu and (Electronic Journal of Plant Breeding, 2018)
The study was conducted with thirty seven advanced rice cultures during Rabi 2016-17 under upland rice ecosystem. The analysis of variance revealed that all the treatments were significant for various characters viz., days to 50% flowering, plant height, number of productive tillers per plant, number of panicles/m2, panicle length, number of filled grains per panicle, grain yield/ha, straw yield/ha and harvest index. The higher magnitude of PCV and GCV were recorded for number of panicles /m2, grain yield/ha and straw yield/ha. High heritability coupled with high genetic advance was recorded for number of panicles/m2 which indicated the major role of additive gene action in the inheritance of this trait. Based on the D2 analysis, the genotypes were grouped into eight clusters. Maximum number of genotypes (21 genotypes) was grouped in cluster I. Maximum inter cluster distance was observed between cluster III and VIII (7.75) followed by between cluster III and VI (7.11) indicating wider genetic diversity between genotypes. The intra cluster distance was maximum in cluster I (4.07) followed by cluster II (3.88) indicates hybridization involving genotypes within the same clusters may result in good cross combinations. Among the nine traits studied, number of panicles/m2 has contributed maximum divergence (22.22%) followed by panicle length (17.12%), plant height (14.41%), filled grains per panicle (11.26%) and days to fifty per cent flowering (10.96%). Hence these altogether contribute more than seventy five per cent towards total divergence. Therefore these characters may be given importance during selection programme in upland rice ecosystem.